Answer:
C. G(x) = (x - 1)² - 3
Explanation:
f(x) + n - shift the graph of f(x) n units up
f(x) - n - shift the graph of f(x) n units down
f(x - n) - shift the graph of f(x) n units to the right
f(x + n) - shift the graph of f(x) n units to the left
===================================
Look at the picture.
The graph of F(x) shifted 1 unit to the right and 3 units down.
Therefore the equation of the function G(x) is
![G(x)=(x-1)^2-3](https://img.qammunity.org/2020/formulas/mathematics/high-school/s77jaldj4h7egdaee5y6veflnt4id7nw0b.png)